20th AIAA International Space Planes and Hypersonic Systems and Technologies Conference 2015
DOI: 10.2514/6.2015-3545
|View full text |Cite
|
Sign up to set email alerts
|

T6: The Oxford University Stalker Tunnel

Abstract: The University of Oxford has embarked on developing the UKs fastest wind tunnel, T6, in collaboration with the University of Queensland (Australia) using technology pioneered by the late Professor Ray Stalker. The T6 facility couples the ex-Australian National University T3 free piston driver to the barrels, nozzles and test section of the Oxford gun tunnel. The facility can operate in three different modes; as a shock tube, a reflected shock tunnel or as an expansion tunnel. The T6 facility will be unique to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 11 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…• T6 Stalker Tunnel, England [15] • HET, USA [16] • HEG, Germany [17] • HELM, Germany [18] • IISc Chemical Kinetics Shock Tube, India [19] Mundt et al reported on the results of using the L1d code to model the T-ADFA, T3…”
Section: Simulations Of Shock Tunnel Facilitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…• T6 Stalker Tunnel, England [15] • HET, USA [16] • HEG, Germany [17] • HELM, Germany [18] • IISc Chemical Kinetics Shock Tube, India [19] Mundt et al reported on the results of using the L1d code to model the T-ADFA, T3…”
Section: Simulations Of Shock Tunnel Facilitiesmentioning
confidence: 99%
“…(decommissioned for use in T6 [15]), T4, and HEG facilities in [5]. Across the four facilities, the L1d code was found to predict the shock speeds and gas pressures quite well.…”
Section: Simulations Of Shock Tunnel Facilitiesmentioning
confidence: 99%
See 3 more Smart Citations